2013
DOI: 10.1371/journal.pone.0073877
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Wrinkle and Anti-Inflammatory Effects of Active Garlic Components and the Inhibition of MMPs via NF-κB Signaling

Abstract: Skin aging is a multisystem degenerative process caused by several factors, such as, UV irradiation, stress, and smoke. Furthermore, wrinkle formation is a striking feature of photoaging and is associated with oxidative stress and inflammatory response. In the present study, we investigated whether caffeic acid, S-allyl cysteine, and uracil, which were isolated from garlic, modulate UVB-induced wrinkle formation and effect the expression of matrix-metalloproteinase (MMP) and NF-κB signaling. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 32 publications
2
107
1
Order By: Relevance
“…This imbalance can cause the excessive concentration of free radicals in body, leading to the oxidative damage of cell membranes, lipids, nucleic acids and proteins, which results in the cell structure and function destruction and occurrence and development of diseases (Blokhina et al, 2003). Garlic has the antibacterial (Farbman et al, 1993), antiviral (Tsai et al, 1985), anti-inflammatory (Kim et al, 2013b), insecticidal (Yang et al, 2009), blood lipid regulating (Bordia et al, 1998), blood glucose decreasing (Bordia et al, 1998), detoxification (Sheen et al, 1996), atherosclerosis preventing (Bordia et al, 1977) and immunity improving (Qiu et al, 2014) functions. It is reported that, the pharmacological effects of garlic are closely related to its antioxidant properties (El-Din et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance can cause the excessive concentration of free radicals in body, leading to the oxidative damage of cell membranes, lipids, nucleic acids and proteins, which results in the cell structure and function destruction and occurrence and development of diseases (Blokhina et al, 2003). Garlic has the antibacterial (Farbman et al, 1993), antiviral (Tsai et al, 1985), anti-inflammatory (Kim et al, 2013b), insecticidal (Yang et al, 2009), blood lipid regulating (Bordia et al, 1998), blood glucose decreasing (Bordia et al, 1998), detoxification (Sheen et al, 1996), atherosclerosis preventing (Bordia et al, 1977) and immunity improving (Qiu et al, 2014) functions. It is reported that, the pharmacological effects of garlic are closely related to its antioxidant properties (El-Din et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[22] We hypothesize that UV-induced expression of MMPs and CatL might be modulated by some common molecular mechanisms. The exact mechanisms need further study.…”
Section: Discussionmentioning
confidence: 99%
“…SAC reduces NFkB transactivation, mRNA expression, and protein production in kidney of diabetic mice via down-regulating p38 and ERK1/2 MAPK pathways (Mong and Yin, 2012). Moreover, SAC, in UVB-induced cell damage, downregulates cFOS and p-cJun (components of AP-1) (Kim et al, 2013). Whether these modifications are taking place in the brain will be a matter of research for a near future.…”
Section: Modification Of Map Kinase Pathwaysmentioning
confidence: 99%
“…It has been reported that SAC inhibits NFkB transactivition and expression in several models: gastric mucosal damage, wrinkle formation, kidney of diabetic mice, endothelial cells, IFNg-stimulated RAW264.7 cell, and human T cells (Geng et al, 1997;Kim et al, 2001;Ho et al, 2001;Ide and Lau, 2001;Mong and Yin, 2012;Kim et al, 2013;Park et al, 2014). Hence, SAC could modify NFkB transactivitation and expression by three mechanisms: 1) inhibition of IKKb kinase activity, 2) modifying MAP kinase pathways, and 3) histone deacetylase (HDAC) inhibitor activity.…”
Section: Sac and Transduction Systems: Inhibition Of Nfkb Activationmentioning
confidence: 99%